The last line of a proof represents <span>the conclusion. The correct option among all the options that are given in the question is the third option or the penultimate option. The other choices can be easily neglected. I hope that this is the answer that has actually come to your desired help.</span>
x + 7 = 2(3x - 4) Remove the brackets
x + 7 = 2*3x - 4*2
x + 7 = 6x - 8 Subtract 7 from both sides.
x + 7 - 7 = 6x - 8 - 7
x = 6x - 15 Subtract 6x from both sides
x - 6x = - 15
-5x = - 15 Divide by -5
-5x/-5 = -15/-5
x = 3
Answer:
Yuhh the answers c dawhggg trus me i just did the same thing lawl!
Step-by-step explanation:
Answer:
i think either b c d
Step-by-step explanation: